The structure and migration patterns of the population of Uruguay through isonymy. Issue 2 (8th March 2020) - Carrieri, A.; Sans, M.; Dipierri, J. E.; Alfaro, E.; Mamolini, E.; Sandri, M.; Rodríguez-Larralde, A.; Scapoli, C.; Barrai, I.
Abstract: Surname distribution can be a useful tool for studying the genetic structure of a human population. In South America, the Uruguay population has traditionally been considered to be of European ancestry, despite its trihybrid origin, as proved through genetics. The aim of this study was to investigate the structure of the Uruguayan population, resulting from population movements and surname drift in the country. The distribution of the surnames of 2, 501, 774 people on the electoral register was studied in the nineteen departments of Uruguay. Multivariate approaches were used to estimate isonymic parameters. Isolation by Distance was measured by correlating isonymic and geographic distances. In the study sample, the most frequent surnames were consistently Spanish, reflecting the fact that the first immigration waves occurred before Uruguayan independence. Only a few surnames of Native origin were recorded. The effective surname number ( α ) for the entire country was 302, and the average for departments was 235.8 ± 19. Inbreeding estimates were lower in the south-west of the country and in the densely populated Montevideo area. Isonymic distances between departments were significantly correlated with linear geographic distance ( p < 0.001) indicating continuously increasing surname distances up to 400 km. Surnames form clusters related to geographic regions affected by different historical processes. The isonymic structure of Uruguay shows a radiation towards the east and north, with short-range migration playing a major role, while the contribution of drift, considering the small variance of α, appears to be minor.